Wpływ poprawnej emisji głosu na interpretację utworu. Próba stworzenia spójnego obrazu na podstawie wiedzy studentów Akademii Muzycznej im. I. J. Paderewskiego w Poznaniu = The influence of proper vocal technique on the quality of ones performance - an attempt to create an overview based on the knowledge of the students of I. J. Paderewski Academy of Music in Poznan - Koczurko, Aleksandra; Stecka, Laura (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
The survey has its purpose in generalisation of students knowledge on the correct vocal technique as well as the process of preparing a musical piece from first reading to its first public performance. Generalized definition of vocal technique contains a detailed description of the physiological process which shows a very high level of consciousness of these processes amongst young singers.
Keywords: emisja głosu; interpretacja utworu; studenci; wokalistyka; śpiew solowy; voice emission; interpretation of a musical piece; students; vocalism; classical singing